Interleukin 10 and transforming growth factor‐beta 1 plasma levels in atopic dogs before and during immunotherapy. (23rd December 2021) - Martini, Franco; Rostaher, Ana; Favrot, Claude; Fischer, Nina
Abstract: Background: Human studies suggest that the cytokines, interleukin 10 (IL‐10) and transforming growth factor‐beta 1 (TGF‐ß1) may play an important role in allergen‐specific immunotherapy (ASIT). However, there is little known about the function of these cytokines in atopic dogs. This study compared the plasma levels of IL‐10 and TGF‐ß1 in atopic and control dogs and investigated their changes during different ASIT approaches. Methods: A total of 54 atopic and 32 control dogs were included. Immunotherapy was performed in 30 atopic dogs. The dogs undergoing immunotherapy were allocated to four groups of different ASIT approaches (namely subcutaneous, intralymphatic, sublingual ASIT and subcutaneous ASIT with recombinant allergens). Blood samples were collected at four timepoints throughout the one year of ASIT. Canine atopic dermatitis extent and severity index, pruritus visual analogue scale and medication score were recorded at each timepoint. Commercially available ELISA kits were used to quantify IL‐10 and TGF‐ß1 in plasma. Results: There was no significant difference in IL‐10 and TGF‐ß1 between atopic and control dogs. The IL‐10 levels were significantly increased in the intralymphatic group at the end of the study. No significant differences were found in the other groups for both IL‐10 and TGF‐ß1. Conclusion: The findings of this work suggest that IL‐10 and TGF‐ß1 cannot be used to monitor the course of the disease during ASIT.